Chocolate confidential - Cuttler, Marcy; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2007)
This program takes you behind the closed doors of the major chocolate corporations and master chocolatiers, examing both chocolate as a food and chocolate professionals as an industry. Meet a cocoa connoisseur as she travels to the Dominican Republic is search of the perfect cocoa bean. Go behind the scenes into the secretive Mars factory and watch millions of M&Ms roll off the assembly line. This program will help students understand the myths and marketing behind one of the world's most complex and versatile foods.'--edited from VEA website
Executive producer, Susan Dando ; editor, Ilona Crabbe ; director of photography, Michael Sweeney
Narrator: Caroly Larson
DVD format
Keywords: Chocolate industry; Chocolate industry -- Marketing; Chocolate candy